Optimizing Surgical Scheduling Through Integer Programming and Robust Optimization - Geranmayeh, Shirin (Université d'Ottawa / University of Ottawa, 2015)
This thesis proposes and verifies a number of optimization models for re-designing a master surgery schedule with minimized peak inpatient load at the ward. All models include limitations on Operating Rooms and surgeons availability. Surgeons` preference is included with regards to a consistent weekly schedule over a cycle. The uncertain in patients` length of stay was incorporated using discrete probability distributions unique to each surgeon. Furthermore, robust optimization was utilized to protect against the uncertainty in the number of inpatients a surgeon may send to the ward per block. Different scenarios were developed that explore the impact of varying the availability of operating rooms on each day of the week. The models were solved using Cplex and were verified by an Arena simulation model.
Keywords: Mixed Integer Programming; Robust Optimization; Master Surgery Schedule